Economic Growth and Financial Instability: The Ideas of Hayek and Keynes - Orlik, Noemi Levy (Journal of Reviews on Global Economics, 2015)
Complex monetary systems in capitalist economies, whose financial markets can cause financial instabilities and economic downturns is an accepted argument by both John M. Keynes and Friedrich A. Hayek, disagreeing in terms of the factors generating financial instability, the mechanism in which financial variables affect the real sector, and more importantly how to generate economic growth. In this paper we discuss Hayek and the Austrian monetary school innovative ideas in terms of money in capitalist economies (i.e., liquidity provisions and credit devaluations) from where the monetarism and later the New Classical framework developed; and revise Keynes and Post Keynesian views that recognized the full effects of money in productions arguing that debts precede money, which is non neutral, thereby can expand economic activity but also unfold financial instability. We concentrate in the dissenting views over financial instability and argue that the main way to overcome economic activity is through expansive fiscal policies, opposing wages cuts, along financial market regulation.